Impact of 24-h feed or water, or both, deprivation on feed intake, metabolic, and inflammatory response in beef heifers. (27th September 2018) - Rett, B; Marques, R S; Brandão, A P; de Sousa, O A; Schumaher, T F; Cooke, R F; Bohnert, D W
Abstract: This experiment evaluated the effects of 24-h feed or water, or both, restriction on hay intake, metabolic, and inflammatory response in growing beef heifers. Forty Angus × Hereford heifers were ranked by initial body weight (BW) (275 ± 6 kg) and age (278 ± 6 d) and randomly allocated to 20 drylot pens (two heifers per pen) in 5, consecutively run, 4 × 4 Latin squares containing four periods of 17 d each. From days 5 to 0 of each period, all pens were offered alfalfa-grass hay ad libitum plus 454 g of dried distillers' grains with solubles (as-fed basis) per heifer/d. On day 0 of each period, pens received one of the four treatments: 1) feed and water restriction for 24 h (FWR ), 2) feed restriction for 24 h (FR ), 3) water restriction for 24 h (WR ), or 4) full access to feed and water (CON ). Treatments were concurrently applied from days 0 to 1. Heifer full BW was collected for two consecutive days (days 6 and 5), before (day 0) and after (day 1) treatment application, and on days 3, 6, and 10 of each period. Hay dry matter intake was recorded daily from days 5 to 10. Blood was collected on days 5, 0, 1, 3, 6, and 10 of each experimental period. Following treatment on day 1, BW loss was greater, and heifer BW was less ( P < 0.01), for WR, FWR, and FR compared with CON, whereas similar ( P > 0.13) for BW loss and heifer BW among heifers that received nutrient restriction. No treatment effects were detected ( P = 0.88) for overall ADG. Plasma cortisol concentration was greater ( P < 0.01) in FR and FWR vs. WR and CON on day 1, and similar ( P = 0.46) between CON and WR. Serum NEFA concentration was greater ( P < 0.01) in FR and FWR vs. WR and CON on day 1, and also greater ( P < 0.01) in WR vs. CON heifers on day 1. No treatment effects were detected ( P = 0.53) for plasma haptoglobin concentration. Hence, feed or water, or both, restriction for 24 h did not affect hay intake and ADG, whereas metabolic results suggest that nutrient deprivation is the major contributor to the increased cortisol and NEFA response of growing beef heifers.